Perlindungan Buah Jambu Kristal dari Serangan Lalat Buah Sebagai Optimalisasi Kualitas di Desa Tamanagung Kecamatan Cluring Kabupaten Banyuwangi - Tri Wahyu Saputra; Wildan Muhlison; Suci Ristiyana; Ika Purnamasari; Yagus Wijayanto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Tamanagung Village, Cluring District, Banyuwangi Regency is one area that cultivates crystal guava fruit for markets in areas in East Java and even big cities in Indonesia. However, one of the difficulties for farmers is to maintain good quality crystal guava and meet market criteria such as crunchy texture, sweetness, slightly runny, no spots, not rotten and free from maggots. Crystal guava fruit can be sold for Rp. 5,000.00 to Rp. 6,000.00 per kilogram but can drop dramatically if there is a decrease in fruit quality. In this service, fruit cover was chosen as this technology to protect crystal guava fruit (Psidium guajava) from fruit fly (Bactrocera spp.) attacks. The focus of this service program is the use of technology that is simple but can be applied quickly by farmers and has a real impact on cultivation results. Protection provides better yields such as avoiding fruit defects, is of higher quality and will increase the selling value of crystal guava fruit. In the end, this program will be able to increase the economic welfare of crystal guava farmers. It is hoped that the positive impact felt by farmers in community service locations can also be felt by farmers in other areas.